The factors affecting investment intentions for employees of PT Bank Central Asia, Tbk. - Semeru, Daniella Mayuni; Negoro, Dimas Angga (Universitas Dian Nuswantoro Semarang, 2024)
This research was conducted to analyze the effect of Personality Traits, Financial Literacy, and Risk Tolerance on Investment Intentions in environmentally friendly companies with Risk Tolerance as a moderating variable, providing input for environmentally friendly companies so they can be more attractive to investors, and contribute to the science of financial management by developing an understanding of the Investment Intentions variable in environmentally friendly companies. This research used quantitative method. The sample is 280 respondents with purposive sampling technique to the employees of PT Bank Central Asia, Tbk. Data was analyzed with Structural Equation Modelling-Partial Least Square (SEM-PLS). The results are personality traits, financial literacy, and risk tolerance had effect on investment intentions and risk tolerance had a moderating effect between financial literacy and investment intentions. With this research, it is hoped that environmentally friendly companies will manage their companies well and do environmentally friendly things included in its annual report so that potential investors are interested in investing in environmentally friendly companies. This research also expected to enrich the knowledge of financial management by providing an understanding of the Investment Intentions variable in environmentally friendly companies. Keywords:environmentally friendly company financial literacy, risk tolerance, investment intentions, personality traits